Ablation of Enpp6 Results in Transient Bone Hypomineralization. (8th December 2020) - Dillon, Scott; Suchacki, Karla; Hsu, Shun‐Neng; Stephen, Louise A; Wang, Rongling; Cawthorn, William P; Stewart, Alan J; Nudelman, Fabio; Morton, Nicholas M; Farquharson, Colin
ABSTRACT: Biomineralization is a fundamental process key to the development of the skeleton. The phosphatase orphan phosphatase 1 (PHOSPHO1), which likely functions within extracellular matrix vesicles, has emerged as a critical regulator of biomineralization. However, the biochemical pathways that generate intravesicular PHOSPHO1 substrates are currently unknown. We hypothesized that the enzyme ectonucleotide pyrophosphatase/phosphodiesterase 6 (ENPP6) is an upstream source of the PHOSPHO1 substrate. To test this, we characterized skeletal phenotypes of mice homozygous for a targeted deletion of Enpp6 ( Enpp6 −/− ). Micro‐computed tomography of the trabecular compartment revealed transient hypomineralization in Enpp6 −/− tibias ( p < 0.05) that normalized by 12 weeks of age. Whole‐bone cortical analysis also revealed significantly hypomineralized proximal bone in 4‐ but not 12‐week‐old Enpp6 −/− mice ( p < 0.05) compared with WT animals. Back‐scattered SEM revealed a failure in 4‐week‐old trabecular bone of mineralization foci to propagate. Static histomorphometry revealed increased osteoid volume ( p > 0.01) and osteoid surface ( p < 0.05), which recovered by 12 weeks but was not accompanied by changes in osteoblast or osteoclast number. This study is the first to characterize the skeletal phenotype of Enpp6 −/− mice, revealing transient hypomineralization in young animals compared with WT controls. These data suggest that ENPP6 is important for bone mineralization and may function upstream of PHOSPHO1 as a novel means of generating its substrates inside matrix vesicles. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.